If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 19 + -22x = 4 + -10x + -4 Reorder the terms: 19 + 9x + -22x = 4 + -10x + -4 Combine like terms: 9x + -22x = -13x 19 + -13x = 4 + -10x + -4 Reorder the terms: 19 + -13x = 4 + -4 + -10x Combine like terms: 4 + -4 = 0 19 + -13x = 0 + -10x 19 + -13x = -10x Solving 19 + -13x = -10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10x' to each side of the equation. 19 + -13x + 10x = -10x + 10x Combine like terms: -13x + 10x = -3x 19 + -3x = -10x + 10x Combine like terms: -10x + 10x = 0 19 + -3x = 0 Add '-19' to each side of the equation. 19 + -19 + -3x = 0 + -19 Combine like terms: 19 + -19 = 0 0 + -3x = 0 + -19 -3x = 0 + -19 Combine like terms: 0 + -19 = -19 -3x = -19 Divide each side by '-3'. x = 6.333333333 Simplifying x = 6.333333333
| (5y-1)=(-2y+4) | | x^2-6x-37=0 | | 0.7(7x+8)=2.7-(x-3) | | 5x+1(-5+2)=18-3 | | 4sqrt(x^2+2x)=4sqrt(3) | | 2x^2-3=x^2+6x | | 5y-7=-169 | | 7n-93=2n-13 | | 4g-3=1g+37 | | X^2+2mx+1=0 | | 23-5n=-3(3-n) | | 17=-7+3n | | x^3-2x=5 | | 9+7=n | | 2*(3x+4)=8*(2x-4) | | (3x^2+x+1)+(2x^2-3x-5)= | | 6z-3=z+7 | | (3y+7)=4 | | 8x+3=-9x-5 | | 6x+131=3x+184 | | 0.75y+9=0.5 | | 4c^3+4c^2-24=0 | | a^2+6a-63=0 | | p(t)=-2t^2+48t+30 | | 9x-3-4x=x+8+x | | 7(2x)-(10-3x)= | | p(t)=-2t+48t+30 | | h=vt-gt | | 6x-2-2x=x+7+x | | 15(-42x-40)=15(-8x+244) | | 8x=2-x^2 | | 6(x-7)+3(x+14)+2(x-15)=-9(x-4)+3(x+7) |